Trees in grassland: the influence of trees on grass production within sylvopastoral systems of the Atlantic Zone of Costa Rica - Kampen, P. (1996)
64 páginas, 11 figuras, 5 tablas, 43 ref. También como serie: Field Report - Atlantic Zone Programme (CATIE); no. 149